A quantitative spatial methodology to delimit urban areas – a case study from Portugal - Soares, M. E. S. (2020)
Delimiting urban areas is crucial for planning and managing cities. In Portugal, urban limits are exclusively decided at the municipal level according to the strategic vision of each municipality. Consequently, urban delimitation is a significantly changeable process. This paper presents a methodology to fill this gap aiming at delimiting urban areas based on objective and quantitative spatial data. A hybrid methodology combining morphological with demographic and land cover data is proposed to delimit urban boundaries. The methodology, which was based on using the most disaggregated spatial units ? the census tracts, was applied in Guarda, a medium-sized Portuguese city. The obtained urban boundary shows a suitable spatial adjustment considering the consolidated urban area. The identified surrounding settlements were used to define expansion areas by fostering development towards these urban areas. In terms of planning, the method can be helpful in designing/revising municipal master plans and in implementing more sustainable planning policies. The described method could be useful for managing and evaluating the city?s needs in a more efficient way.